Evaluation Of Several Chemical Control Approaches Against Bagworm, Metisa Plana Walker (Lepidoptera: Psychidae) In Felda Oil Palm Plantations - Salim, Hasber (2010)

(untitled)
In oil palm plantations chemical control is still the principal means of reducing pest numbers when their population levels are high. In this study, a series of field trials investigating the efficacy of several application techniques for insecticides against bagworm, Metisa plana, were carried out in oil palm plantations. The efficacy of the ground spraying technique for four insecticides (trichorfon, lambda cyahothrin, cypermethrin EC and cypermethrin EW) as well as a bio insecticide,